Pacific pidgins and creoles : origins, growth and development - Tryon, D. T. (Darrell T.) (Trends in linguistics. Studies and monographs, 2011)
Pacific Pidgins and Creoles discusses the complex and fascinating history of English-based pidgins in the Pacific, especially the three closely related Melanesian pidgins: Tok Pisin, Pijin, and Bislama. The book details the central role of the.